LDH hybrid thermosensitive hydrogel for intravaginal delivery of anti-HIV drugs. Issue 1 (4th December 2019) - Tian, Wenxue; Han, Shangcong; Huang, Xia; Han, Mei; Cao, Jie; Liang, Yan; Sun, Yong
Abstract: Microbicides based on hydrogel have become an effective way to prevent the HIV replication and transmission because of their convenience and prolonging drug release. In this study, a hybrid thermo-sensitive hydrogel constituted by nanosized layered double hydroxides and poloxamer 407 (P407) was constructed and co-loaded with both hydrophobic and hydrophilic drug. The LDH-P407 hydrogel could achieve sol–gel transition at body temperature. The in vivo experiment showed that LDH-P407 hydrogel can achieve controlled release of theaflavin and Nile red (hydrophobic drug model) into blood by vaginal drug delivery, meanwhile the hydrogel showed barely mucosal irritation. In addition, ex vivo experiment showed that the nifeviroc-loaded LDH-P407 hydrogel was able to specifically bind co-receptor CCR5 of DCs cells. Therefore, the LDH-P407 hydrogel would be a promising carrier for intravaginal delivery of anti-HIV drugs.